MARINATION EFFECTS OF GARLIC EXTRACT (Allium Sativum L.) AND GARLIC POWDER ON THE PHYSICAL AND ORGANOLEPTIC PROPERTIES OF SPENT HEN CHICKEN MEAT - K. W, Floriantini; Okarini, I. A.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
This study aims to determine the length of marination with garlic extract ( Allium sativum L .) and garlic powder on the physical and organoleptic properties of spent laying hens meat. This study was conducted at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry. The design used was a factorial randomized block design (RBD) with 2 x 2 treatments and 4 replications. The first group was the treatment of 10% marination of garlic extract and garlic powder and the second group was the marination time of 1.5 hours and 3 hours. Data analysis used the variance test. The results of the study in the treatment group and the time group showed that there were significant differences (P<0.05) in the organoleptic test (color, aroma, texture, and overall acceptance) and pH values. Then there was no significant difference (P>0.05) in the taste and cooking losses. The interaction between treatment and marination time was significantly different (P<0.05) in the organoleptic test (color and taste). Based on the results of the study, it can be concluded that the treatment of discarded laying hens with fresh garlic and 3 hours of marinating time can improve the organoleptic quality and reduce the pH value and cooking loss of the meat.   Keywords:  garlic, spent laying chicken meat, long marination, physical quality, and organoleptic test